2015
DOI: 10.1080/14786435.2015.1043969
|View full text |Cite
|
Sign up to set email alerts
|

Surface characteristics and electrochemical behaviour of sputter-deposited NiTi thin film

Abstract: Thin nanocrystalline amorphous NiTi film was deposited on Si substrate using DC magnetron sputtering. The as-deposited NiTi thin film was crystallized by heat treatment at 500°C for 1 h. The crystal structure, surface morphology, microstructure and surface chemistry of the deposited films were studied using X-ray diffraction, atomic force microscopy, scanning electron microscopy and X-ray photoelectron spectroscopy (XPS), respectively. Corrosion behaviour was assessed in Ringer's solution at 37°C by open circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…It can be concluded that the presence of alumina in ODS, improve the corrosion resistance along with the upgrading the mechanical properties. It is reported that [18] the presence of inhomogeneous particles in the alloys weaken the corrosion resistance but here, because of having nano-sized grains, the effect of passivation is more than that of galvanic corrosion. The Tafel calculation results and the breakdown potentials obtained from the potentiodynamic anodic polarization tests in 3.5% NaCl solution are given in Table 2.…”
Section: Resultsmentioning
confidence: 87%
“…It can be concluded that the presence of alumina in ODS, improve the corrosion resistance along with the upgrading the mechanical properties. It is reported that [18] the presence of inhomogeneous particles in the alloys weaken the corrosion resistance but here, because of having nano-sized grains, the effect of passivation is more than that of galvanic corrosion. The Tafel calculation results and the breakdown potentials obtained from the potentiodynamic anodic polarization tests in 3.5% NaCl solution are given in Table 2.…”
Section: Resultsmentioning
confidence: 87%
“…Moreover, the bulk nitinol will lose its shape memory and superelasticity in the amorphous conditions. On the other hand, homogeneous and dense amorphous TiNi films can be readily sputter-deposited onto the substrate, such as nitinol at an ambient temperature, thus the corrosion resistance could be improved significantly [5,8,25]. However, there is no systematic report on the corrosion performance of the sputtered TiNi films.…”
mentioning
confidence: 99%
“…According to Oliveira et al [64], this behavior is characteristic of metals that present spontaneous formation of a passive film on the metallic surface, that is, that undergo passivation, being able to control and reduce the dissolution of the alloy. Saebnoori et al [65] clarify that, during immersion in an electrolyte, dissolved oxygen ions adsorb on the surface of the electrode and react with ions of the metallic alloy to form an oxide layer, which inhibits the conductivity of ions at the electrode/electrolyte interface, so, forming a protective film. As a result, there is a decrease in the anodic dissolution current, as indicated by the increase in E OCP , reaching a stable condition after the completion of passive film formation.…”
Section: Corrosion Resistance Evaluationmentioning
confidence: 99%